Oproer in de letteren Sixties-protest in de Lage Landen - Debergh, Gwennie; Janssens, Nele; De Taeye, Lieselot (SEL, 2021)
Our collective memory still associates the sixties with protest culture, but the legacy of the demonstrations is a topic of discussion to date. There is no shortage of myths about the sixties, but many facts and details remain unknown, including knowledge concerning literature of that time. Oproer in de letteren wants to offer insight into the complexity of the revolts by showing a contemporary perspective on the material. From Hugo Claus and racism to lyrics to pornography: the works in this book readjust the clichéd image of a defining period and show how Dutch literature interacted with an extraordinary decade.